What happened to goodbye - Dessen, Sarah (New York : Viking Childrens Books, 2011)
Following her parents' bitter divorce as she and her father move from town to town, seventeen-year-old Mclean reinvents herself at each school she attends until she is no longer sure she knows who she is or where she belongs.
Keywords: Divorce -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction